PELATIHAN CANVA SEBAGAI MEDIA PROMOSI PADA SISWA/I SMK PARIWISATA CITAYAM - Faridah Faridah; Nurlina Nurlina; Yoeliastuti Yoeliastuti; Herry Syafrial; Edi Wahyu Wibowo (POLITEKNIK LP3I JAKARTA, 2022)
In the era of industrial technology 4.0, technology media is increasingly being used in trade and business activities. The internet is a part of human life in the use of promotional media, because any media uses the internet a lot. One of the platforms that is currently in great demand is Canva media. Canva makes graphic design and publishing content easier and faster than any other graphic software. The problem that occurs to students at Citayam Tourism Vocational School is the lack of understanding of students about the Canva application as a digital media. The purpose of this service is as a solution in increasing the knowledge of students and teachers who take part in the training to better understand the importance of promotional media in the era of technology that is more effective and efficient in its delivery. This Community Service activity is carried out using lecture, question and answer methods and demonstrations. As a result of this activity, participants can receive knowledge and can use the Canva application in promotional activities. Community service implementation activities are carried out in stages, namely by communicating with the school in order to find out the weaknesses and needs of learning materials. The second stage is to carry out material giving activities that are carried out online by training students using the Canva application.Keywords: Training, Canva, Promotion